Characteristics study of open cathode PEM fuel cell for portable and stationary power sources - Phua, James Shau Chong. (2009)
As high demand in energy, depleting fossil fuel and environmental hazard continues, the searching for alternative, renewable and clean energy for the future become ever important in this era. Many research and development have been done to find the solutions for clean energy. One of the potential candidates for renewable, clean energy is fuel cell. As it produce zero emission and high efficiency device, lot of applications have been developed using fuel cell as the main power source. Portable and stationary power source are one of the many applications that has been on research as the replacement of traditional batteries and power source that run on fossil fuel. This report are mainly focus on the open cathode fuel cell stack which draws oxidants from the surrounding air using a fan mounted on the fuel cell stack. Several experiments have been conducted to understand the characteristics of an open cathode fuel cell stack. Different operational conditions and states such as pressure, flow rate, temperature, steady state (polarization curve) and transient state are the experiment areas that are focused on. Constant load test are also conducted to understand the behavior of the fuel cell under such condition, and also studies on dead end mode operation is also done as it plays a significant role in the performance of the fuel cell. Flooding and thermal factors of the fuel cell stack are also studied.